External debt determinants: Do macroeconomic and institutional ones matter for selected ASEAN developing countries? - Edi Harsono; Andi Kusumawati; Nirwana Nirwana (Economies, 2023)
Developing nations have the task of effectively managing their external debt. The government is urged to comprehend the decisive component in managing its external debt, despite the varying viewpoints among economists. In addition, the world sees the need for institutional quality to optimize its economic policy. Institutional quality shows accountability, stability, effectiveness, quality, law, and trust. Our research examines the determinant factors of external debt and discusses the policy to manage external debt. We regress the inflation rate, exchange rate, interest rate, trade openness, and institutional quality on external debt. This study also uses moderated regression analysis to examine the interaction between institutional quality and macroeconomic indicators on external debt. We selected 52 samples from five ASEAN developing countries from 2008 to 2019. The first study found that the inflation rate, interest rate, and institutional quality have a negative impact on external debt, while the exchange rate and trade openness have a positive impact on external debt. Next, we were surprised that institutional quality could not moderate the relationship between the inflation rate, exchange rate, and interest rate on external debt. Further, it only moderated the relationship between trade openness and external debt. In the end, we discuss the external debt determinants from the selected ASEAN developing countries with the theories.
Keywords: 330; external debt; macroeconomic indicator; institutional quality; inflation rate; exchangerate; interest rate; trade openness